The brain renin-angiotensin system and cardiovascular responses to stress: insights from transgenic rats with low brain angiotensinogen - Arnold, Amy C. (American Physiological Society, 2012)
The renin-angiotensin system (RAS) has been identified as an attractive target for the treatment of stress-induced cardiovascular disorders. The effects of angiotensin (ANG) peptides during stress responses likely result from an integration of actions by circulating peptides and brain peptides derived from neuronal and glial sources. The present review focuses on the contribution of endogenous brain ANG peptides to pathways involved in cardiovascular responses to stressors. During a variety of forms of stress, neuronal pathways in forebrain areas containing ANG II or ANG-(1–7) are activated to stimulate descending angiotensinergic pathways that increase sympathetic outflow to increase blood pressure. We provide evidence that glia-derived ANG peptides influence brain AT(1) receptors. This appears to result in modulation of the responsiveness of the neuronal pathways activated during stressors that elevate circulating ANG peptides to activate brain pathways involving descending hypothalamic projections. It is well established that increased cardiovascular reactivity to stress is a significant predictor of hypertension and other cardiovascular diseases. This review highlights the importance of understanding the impact of RAS components from the circulation, neurons, and glia on the integration of cardiovascular responses to stressors.